ON THE QUESTION OF ETHNO-LINGUISTIC CONTACTS OF MOUNTAIN JEWS WITH THE PEOPLES OF THE NORTH CAUCASUS (BASED ON ANTHROPONYMIC MATERIALS) - Murzahanov, Urij Isaevic (History, Archeology and Ethnography of the Caucasus, 2021)
The purpose of our research is to study the specifics of ethnolanguage contacts between mountain Jews and the peoples of the North Caucasus, which allows us to trace the ethnocultural Parallels that existed in the past between them. As you know, language is an important historical source, and since language communication involves interaction between members of an ethnic group, ethnographic group, or subethnos, it can be stated that each language is characterized by the totality of all forms of its existence: a spoken language with its division into territorial dialects, a literary language in oral and written varieties, a special cult language, etc. Accordingly, studies on the language contacts of mountain Jews with the peoples of the North Caucasus (of course, structurally diverse and genetically unrelated peoples) are of great value from the point of view of not only linguistics, but also history and Ethnography. The study of the anthroponic Fund of the North Caucasian mountain Jews is also of great interest in this regard. Anthroponymy, due to its special functional nature, is subject to rapid changes, and its composition is heterogeneous. The mountain Jews of the North Caucasus attached special importance to the naming ceremony. In the second half of the XIX – early XX century, the anthroponymicon of mountain Jews was dominated by Jewish names, but in addition to them, there was also a significant layer of names of Persian and Turkic origin, as well as names that arose on the mountain-Jewish soil proper. During the Soviet period, borrowed names (of Latin, Greek, and Slavic origin) became the predominant foreign-language names among the mountain Jews of the North Caucasus, which is typical for almost all the Caucasian peoples of the Caucasus.